Cotton pollen gemination in vitro. III. Gibberellic acid effect - Almeida, Francisco Célio Guedes; Silva, José Fortunato da; Alves, José Ferreira; Silva, Fanuel Pereira da; Almeida, Francisco Aécio Guedes (Pesquisa Agropecuaria Brasileira, 2014)
The effect of gibberellic acid upon cotton (Gossypium hirsutum L.) pollen germination was studied under in vitro conditions. In this study, gibberellic acid was added in five concentrations (0, 25, 50, 100, and 200 ppm) to a basal medium containing, in aquous solution, 1% agar, 15% sucrose, 0,09% manganous sulfate, 0,03% boric acid, 0,06% calcium nitrate, and pH adjusted to 7. Up to 50 ppm level, gibberellic acid did not show any effect on poilen germination. A significant reduction of percent germination was observed when 100 ppm gibberellic acid was added. When AG3 was not present in the medium, the pollen tube length was 692,2 mis